Of apples and oranges: Lessons learned from the preparation of research protocols for systematic reviews exploring the effectiveness of Specialist Palliative Care. Issue 1 (December 2016) - Gaertner, Jan; Siemens, Waldemar; Daveson, Barbara; Smith, Melinda; Evans, Catherine; Higginson, Irene; Becker, Gerhild
Abstract Background Agreed terminology used in systematic reviews of the effectiveness of specialist palliative care ((S)PC)) is required to ensure consistency and usability and to help guide future similar reviews and the design of clinical trials. During the preparation of protocols for two separate systematic reviews that aimed to assess the effectiveness of SPC, two international research groups collaborated to ensure a high degree of methodological consensus and clarity between reviews. During the collaboration, it became evident that close attention is needed to (i) avoid ambiguity in the definition of advanced illness, (ii) capture the specialist expertise and prerequisites for SPC interventions, and (iii) the multi-professional and multi-dimensional nature of PC. Also, (iv) the exclusion of relevant studies or (v) impracticality of meta-analyses of the obtained data must be avoided. The aim of this article is to present the core issues of the discussion to help future research groups to easily identify potential pitfalls and methodologic necessities. Core issue discussion Core issues that arose from the discussion are presented along the research questions according to the PICO process: Population (P): Authors should refer to existing definitions of PC to ensure that, even if the review aims to investigate specific patients (e.g. cancer patients), it is important to make clear that PC is applicable for all life-limiting diseases and not limited to end-of-life or cancer. Intervention (I): PC is a core responsibility of all disciplines (general PC). In contrast, SPC demands further training and expertise. Therefore, core tenets of SPC interventions are that they are (i) multi-professional and (ii) aim at the multi-dimensional nature of suffering. Outcome (O): The main goal of PC is multi-dimensional (quality of life, suffering or distress). Yet, meta-analysis may be complex to conduct due to the heterogeneity of the multi-dimensional outcomes. Therefore, the assessment of uni-dimensional measures such as pain can also provide clinically relevant information that is easier to obtain. Discussion and conclusion Recommendations for future systematic reviews and clinical trials include: (i) Appraise the experience of other research groups who have produced similar systematic reviews or clinical trials. (ii) Include studies that meet the multi-professional and multi-dimensional nature of PC and the specialization requirements for SPC. (iii) Thoroughly weigh relevance and practicability of the primary outcome. Multi-dimensional tools such as quality-of-life questionnaires assess the different dimensions of suffering (the true scope of PC), but uni-dimensional measures such as pain are easier to assess in meta-analyses.